Efficient and stable planar perovskite solar cells with carbon quantum dots-doped PCBM electron transport layer. (26th April 2019) - Zhu, Xiaomeng; Sun, Jing; Yuan, Shuai; Li, Ning; Qiu, Zhiwen; Jia, Jinbiao; Liu, Yining; Dong, Jia; Lv, Pin; Cao, Bingqiang
Abstract : The solar cell with carbon QDs-doped PCBM as its electron transporting layer shows the highest PCE of 18.1%. Abstract : Perovskite solar cells with a single light absorption heterojunction has demonstrated a power conversion efficiency of as high as 23.2% in the past few years. In this work, for the first time, we used quasi-spherical carbon quantum dots (CQDs)-doped PCBM film as the electron transporting layer of an inverted perovskite solar cell. The device structure is FTO/PEDOT:PSS/MAPbI3 /PCBM:CQDs/BCP/Ag. The optimized PCE of 18.1% was achieved and a 13% enhancement was observed compared with those of pure PCBM-based devices. Various advanced characterizations including ultrafast spectroscopy, conductive atomic force microscopy, and electronic impedance spectroscopy elucidate that quasi-spherical CQD doping leads to enhanced electrical conductivity, electron mobility, and charge extraction efficiency. Moreover, we find that such CQD doping helps to prevent I − ions from undergoing interface diffusion and thus enhances the stability of solar cells.